PENERAPAN PENDEKETAN CONTEXTUAL TEACHING AND LEARNING (CTL) DALAM MENINGKATKAN KETERAMPILAN SOSIAL SISWA PADA PELAJARAN IPS - Anida Uswatun Hasanah R, Anida; Nurdiansyah; Permas Hikmatunisa, Nenden (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the low social skills of students in social studies learning, especially in relation to daily life. In social studies learning, students have difficulty applying Social Skills. The solution to fix it is to apply Role Playing learning. In order to anticipate this phenomenon, in this study, an approach social studies learning was applied, namely the application of the Contextual Teaching and Learning (CTL) approach in improving students' Social Skills in social studies lessons. In learning that uses this contextual approach strategy, students are directed to think critically and act logically, creatively, innovatively and tolerantly and are able to build cooperation in their groups. The application of the contextual approach in this study is focused on the discovery of events experienced by students themselves as well as their use in solving problems around students in the context of daily life.This research is a Classroom Action Research. The cycle model consists of 2 cycles, each cycle consists of learning planning, implementation of actions, observation, and reflection. The instruments used consisted of interviews, observations, and individual test sheets. The conclusion obtained in this study is that in the initial condition of learning obtained an average score of 65.17, in the first cycle the average score of the pre-test was 67.58 and the post-test score of 87.24 increased by 22.07. In the second cycle, the average score of the pre-test was 87.58 and the post test 91 increased by 3.76. Overall, social studies learning with the application of a contextual approach has experienced a relatively significant increase in social skills both in the student learning process. Keywords: Contextual Teaching and Learning (CTL) approach, role playing learning, social skills